Self-Cleaning Limestone Paint Modified by Nanoparticles TiO2 Synthesized from TiCl3 as Precursors and PEG6000 as Dispersant - Nur Fadhilah; Niki Etruly; Maktum Muharja; Dyah Sawitri (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
Limestone is commonly used for wall painting, but it is easy to be dirty. In this study, a self-cleaning limestone paint was synthesized by modifying dispersant and TiO2 nanoparticles. The TiO2 that prepared by TiCl3 were functionalized with PEG6000 as a surface activating agent. The paint achieved highest impurity degradation of 83.11 % for the mass ratio of TiO2 and PEG6000 (MRTP) of 1: 6, in which TiO2 average size distribution was 75.81 µm2, the particle surface area of TiO2 was 2,544 µm2, and the smallest contact angle was 7°. It was found that the dispersant (PEG6000) significantly improved the self-cleaning ability of limestone paint. The surface tension reduction from PEG6000-modified prevented the agglomeration process of TiO2 and suggests that the limestone paint a good self-cleaning coating for wall painting.